Faktor-Faktor yang Memengaruhi Behavioral Intention to Use Generative AI untuk Pembuatan Konten Media Sosial pada Mahasiswa di Jakarta - Damar Lintang; Diena Noviarini; Meta Bara Berutu (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
This study aims to analyze the factors influencing the behavioral intention to use Generative AI, specifically Google Gemini, for social media content creation among university students in Jakarta. This research integrates the Unified Theory of Acceptance and Use of Technology (UTAUT) with the information quality construct. The study employed a quantitative approach with data collected from 320 students through online questionnaires. Data analysis was performed using PLS-SEM. The findings reveal that effort expectancy, information quality, and attitude have positive and significant effects on behavioral intention, while performance expectancy does not significantly influence behavioral intention. Attitude emerges as the most dominant predictor. These results contribute theoretically to technology acceptance literature and provide practical insights for technology developers and educational institutions in optimizing Generative AI adoption among young creators in Indonesia.